Apathy is associated with poor prognosis in amyotrophic lateral sclerosis. (29th January 2016) - Caga, J.; Turner, M. R.; Hsieh, S.; Ahmed, R. M.; Devenney, E.; Ramsey, E.; Zoing, M. C.; Mioshi, E.; Kiernan, M. C.
Abstract : Background and purpose: Apathy is the most commonly reported behavioural change in amyotrophic lateral sclerosis (ALS). However, the degree to which it affects prognosis and overlaps with depression in this population is unknown. The present study examined the relationship between level of apathy, mortality and survival time and whether apathy was linked to specific symptom clusters of depression. Methods: A cohort of 76 consecutive ALS patients attending specialized multidisciplinary clinics were classified according to level of apathy. The effects of clinical factors and apathy on survival time were analysed using univariate and multivariate methods. Results: The majority of patients with moderate to severe apathy died during the study ( P = 0.003) and had a median survival time of 21.7 months, considerably shorter than patients with mild apathy (46.9 months) and no apathy (51.9 months) ( P = 0.0001). Apathy remained a significant predictor of survival even after controlling for clinical factors and symptom duration at the time of study entry (hazard ratio 3.8, 95% confidence interval 1.9–7.5, P = 0.0001). Depression with demoralization was not associated with level of apathy ( P = 0.172) whereas depression with anhedonia was more common in patients with apathy than in those without apathy ( P = 0.006). Conclusions: The presence of severe apathy is an independent, negative prognostic factor in ALS.